Meditation and the Martial Arts - David O'Regan (Universidad de León, 2012)
Michael L. Raposa. Charlottesville, VA: University of Virginia Press, 2003. 192 páginas, 13,3x 20,3 cm. I.S.B.N.: 08-1392-238-0.